Hakikat Kurikulum Pendidikan Islam - Amanda Ikhwana; Nabila Ritonga; Ummi Hayati Sinaga; Mardinal Tarigan; Marzuki Marzuki (El-Mujtama: Jurnal Pengabdian Masyarakat, 2023)
The organization of learning materials according to a curriculum, which is influenced by teaching and learning activities, is a crucial part of learning planning. A component of religious education that helps it achieve its objectives is the curriculum (Islamic education). The Islamic Education Curriculum attempts to foster moral improvement, knowledge acquisition, and trust in the minds and hearts of the younger generation. Keywords: Curriculum, Islamic Education